Natural Variability in Parent-Child Puzzle Play at Home - Pochinki, Nicole; Reis, Dakota; Casasola, Marianella; Oakes, Lisa M.; LoBue, Vanessa (Frontiers in Psychology, 2021)
Here we observed 3- to 4-year-old children (N = 31) and their parents playing with puzzles at home during a zoom session to provide insight into the variability of the kinds of puzzles children have in their home, and the variability in how children and their parents play with spatial toys. We observed a large amount of variability in both children and parents’ behaviors, and in the puzzles they selected. Further, we found relations between parents’ and children’s behaviors. For example, parents provided more scaffolding behaviors for younger children and parents’ persistence focused language was related to more child attempts after failure. Altogether, the present work shows how using methods of observing children at a distance, we can gain insight into the environment in which they are developing. The results are discussed in terms of how variability in spatial toys and spatial play during naturalistic interactions can help us contextualize the conclusions we draw from lab-based studies.